Floristic analysis of semi-arid mountain ecosystems of the Griqualand West centre of plant endemism, Northern Cape, South Africa - Nanette van Staden; STEFAN JOHN SIEBERT; DIRK PETRUS CILLIERS; DIAN WILSENACH; ARNOLD WALTER FRISBY (Society for Indonesian Biodiversity, 2020)
Abstract. Van Staden N, Siebert SJ, Cilliers DP, Wilsenach D, Frisby AW. 2020. Floristic analysis of semi-arid mountain ecosystems of the Griqualand West centre of plant endemism, Northern Cape, South Africa. Biodiversitas 21: 1989-2002. The Griqualand West Centre (GWC) is one of 13 centres of plant endemism in South Africa. Despite its unique flora, it remains poorly conserved and studied. A recent study identified an extensive geographical core area for the GWC, but endemic plant species were found to be absent from certain parts within these borders. To address this, we refined the current GWC borders based on an ecological niche model, which predicted that endemic species are restricted to four mountain ranges within GWC. Mountain floras within these refined borders were then floristically compared to assess whether they are hotspots of endemicity. Floristically, the Asteraceae, Fabaceae, Malvaceae, and Poaceae were the dominant plant families. Mountain ecosystems differed from one another at species level, with indicator species explaining the compositional differences. Distribution patterns of indicator species were determined by mean annual precipitation, Ca: Mg ratios, soil pH, cation exchange capacity, iron, and sand content. These environmental factors are possible drivers of niche partitioning, environmental filtering and habitat specialization in each mountain ecosystem. Limestone and banded ironstone habitats were identified as conservation priority areas, since they contained the highest numbers of rare and threatened GWC restricted-range species, of which six were narrow endemics.